Strong ESG Risk Management as a Way to Improve Organisational Resilience in Times of Crisis: An Analysis of WIG-ESG Index Constituents - Zaremba, Ulyana (Mocne zarządzanie ryzykiem ESG jako sposób na zwiększenie odporności organizacji w czasach kryzysu: analiza składników indeksu WIG-ESG)
During the last decade sustainable investment practices have evolved significantly. ESG reporting is moving seamlessly from voluntary to mandatory. By investing in companies that score high in ESG rankings, investors hope for the organisation’s resilience to the crisis and higher returns. Due to the dynamic development of socially responsible investing both in Poland and worldwide, new indices using ESG screening criteria are being designed, which in turn are the underlying instrument for structured products. The aim of the study was to analyse the constituents of the newly created WIG-ESG index and to discuss its performance and organisational resilience in relation to ESG risk exposure and management. The research showed that the criteria for inclusion in the WIG- -ESG index should be amended to recognise companies that care about strong ESG risk management and exclude those with negligible ESG efforts. The second important issue is eligibility for inclusion. If all companies are eligible to be included in the index (ESG testing as a condition for inclusion), this will reduce the rotation of the index’s constituents and allow the relation between a company’s ESG score after each update and its long-term performance to be explored.
Financial Sciences. Nauki o Finansach, 2023, vol. 28, no. 1, s. 17-31
Keywords: ESG risk rating; organisational resilience; sustainable investing; ESG equity indices; WIG-ESG; ratingi ESG; odporność organizacyjna; zrównoważone inwestowanie; giełdowe indeksy ESG